Change of the indices of the cytokine status in patients with chronic combined hepatitis B+C in a process of antiviral therapy - O. L. Sobolevskaya (Журнал инфектологии)
The author studied the cytokine status in patients with chronic combined hepatitis B+C in a process of antiviral therapy. The examination embraced 49 patients aged from 18 to 47 years (pegylated interferon- alfa2а and ribavirin were used in 24 patients). It is established, that a significant increase of the interferon-α, interferon-γ, tumor necrosis factor-α (with following decrease of tumor necrosis factor-α) in blood serum content in patients with a stable virusologic response serves as an early criterion of the antiviral therapy effectiveness.